Influence of Temperature from 20 to 100 °C on Specific Surface Energy and Fracture Toughness of Silicon Wafers - V. A. Lapitskaya; T. A. Kuznetsova; S. A. Chizhik (Приборы и методы измерений)
The influence of temperature in the range from 20 to 100 °C on the specific surface energy and fracture toughness of standard silicon wafers of three orientations (100), (110) and (111) was studied. Silicon wafers were heated on a special thermal platform with an autonomous heating controller, which was installed under the samples. At each temperature, the samples were kept for 10 min. The specific surface energy γ after exposure to temperature was determined by atomic force microscopy (AFM). Fracture toughness during and after exposure to temperature was determined by indentation followed by visualization of the deformation region using AFM. It has been established that the specific surface energy γ of Si wafers with orientation (100) and (111) increases with increasing temperature from 20 to 100 °C, and for orientation (110) it increases at temperatures from 20 to 80 °C, and then decreases. The diagonal length d of indentation marks, performed both during the heating process and after heating, decreases by increasing the temperature from 20 to 100 °C. The crack length c decreases on silicon wafers during indentation during heating from 20 to 100 °C, and after exposure to temperature, the length increases. When the plates are exposed to temperature, the fracture toughness KIC increases with increasing temperature: for orientation (100) – up to 1.61 ± 0.08 MPa·m1/2, for (110) – up to 1.60 ± 0.08 MPa·m1/2 and for (111) – up to 1.66 ± 0.04 MPa·m1/2. A direct correlation was established between KIC, measured during  exposure to temperature, and an inverse correlation between KIC measured after exposure to temperature and specific surface energy for the (100) and (111) orientations. An inverse correlation was obtained by KIC at the (110) orientation when exposed to temperatures of 20–40 and 80–100 °C, and after exposure, a direct correlation was obtained. At 60 °C there is no correlation. The results obtained can be used to improve the mechanical properties of silicon wafers used in solar cells and microelectromechanical systems (operating at temperatures up to 100 °C).